Highly Conductive Flexible Conductor Based on PEDOT:PSS/MWCNTs Nano Composite - Fahad Alhashmi Alamer (Crystals, 2023)
Flexible textiles with strong electrical conductivities have enormous potential as active components in wearable electronics. In this study, we fabricated highly flexible electrical conductors based on cotton fabrics using multiwalled carbon nanotubes (MWCNTs) and poly(3,4-ethylenedioxythiophene)/poly(styrenesulfonate) (PEDOT:PSS) nanocomposites. We propose that mixing and drop-casting with different amounts of MWCNTs and a fixed amount of doped PEDOT:PSS using a cotton fabric provides a wide range of conductivities depending on the amount of MWCNTs in the mixture. Scanning electron microscopy (SEM) confirmed that the distribution of MWCNTs in the PEDOT:PSS films coated the surface of the cotton fabric, thereby increasing its electrical conductivity. We found that the amount of MWCNTs significantly affected the electrical properties of the nanocomposite cotton in two ways. First, the sheet resistance of the nanocomposite cotton decreased from 78.35 Ω/□ to 2.86 Ω/□ when the concentration of the nanocomposite was increased from 9.21 wt% to 60.27 wt%. This implies that the electrical properties of the nanocomposite cotton can be adjusted by controlling the amount of MWCNTs in the blend. Moreover, we found that the relationship between the sheet resistance and nanocomposite concentration obeys the power law with an exponent α ~ 1.676. Second, the study of the effect of temperature on the resistance indicates that the conductive nanocomposite exhibits semiconductor behavior in the temperature range 24–120 °C and obeys the variable range hopping model. The characteristic temperatures, resistance prefactor, and density of localized states and activation energies depend on the concentration of MWCNTs and can be described by power laws with exponents of 0.470, −1.292, −0.470 and 0.118, respectively. The novel nanocomposite cotton fabric developed in this study exhibits suitable electrical and thermal properties and good long-term electrical stability, which make the nanocomposite cotton fabric a potential flexible conductor with a wide range of electrical conductivities, making it suitable for various applications.